Phosphatidylinositol phosphate kinase PIPKIγ and phosphatase INPP5E coordinate initiation of ciliogenesis - Xu, Qingwen (Nat Commun, 2016)
Defective primary cilia are causative to a wide spectrum of human genetic disorders, termed ciliopathies. Although the regulation of ciliogenesis is intensively studied, how it is initiated remains unclear. Here we show that type Iγ phosphatidylinositol 4-phosphate (PtdIns(4)P) 5-kinase (PIPKIγ) and inositol polyphosphate-5-phosphatase E (INPP5E), a Joubert syndrome protein, localize to the centrosome and coordinate the initiation of ciliogenesis. PIPKIγ counteracts INPP5E in regulating tau-tubulin kinase-2 (TTBK2) recruitment to the basal body, which promotes the removal of microtubule capping protein CP110 and the subsequent axoneme elongation. Interestingly, INPP5E and its product—PtdIns(4)P—accumulate at the centrosome/basal body in non-ciliated, but not ciliated, cells. PtdIns(4)P binding to TTBK2 and the distal appendage protein CEP164 compromises the TTBK2-CEP164 interaction and inhibits the recruitment of TTBK2. Our results reveal that PtdIns(4)P homoeostasis, coordinated by PIPKIγ and INPP5E at the centrosome/ciliary base, is vital for ciliogenesis by regulating the CEP164-dependent recruitment of TTBK2.